2019
DOI: 10.1186/s11689-019-9273-1
|View full text |Cite
|
Sign up to set email alerts
|

A Brazilian cohort of individuals with Phelan-McDermid syndrome: genotype-phenotype correlation and identification of an atypical case

Abstract: Background Phelan-McDermid syndrome (PMS) is a rare genetic disorder characterized by global developmental delay, intellectual disability (ID), autism spectrum disorder (ASD), and mild dysmorphisms associated with several comorbidities caused by SHANK3 loss-of-function mutations. Although SHANK3 haploinsufficiency has been associated with the major neurological symptoms of PMS, it cannot explain the clinical variability seen among individuals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 25 publications
7
58
1
1
Order By: Relevance
“…100% of children were able to walk but at a delayed age, which is compatible with a different PMS cohort [32]. Lymphedema, hypothyroid, diabetes, vitiligo and enzyme deficiency absent in individuals in our cases have been reported in patients with PMS [5,22,23,27]. Furthermore, there was a remarkable difference in the frequency of certain PMS features (i.e.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…100% of children were able to walk but at a delayed age, which is compatible with a different PMS cohort [32]. Lymphedema, hypothyroid, diabetes, vitiligo and enzyme deficiency absent in individuals in our cases have been reported in patients with PMS [5,22,23,27]. Furthermore, there was a remarkable difference in the frequency of certain PMS features (i.e.…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, hearing loss reported in 3% of cases with PMS, were uncommon [27]. Lymphedema, hypothyroid, diabetes, vitiligo and enzyme deficiency have been reported in patients with PMS [5,22,23,27], but were absent in individuals in our cases (Table 3).…”
Section: Other Clinical Featuressupporting
confidence: 67%
“…A genotype-phenotype study of 71 patients showed an association between increased deletion size and 16 features [ 4 ]. Samogy-Costa et al found that renal abnormalities, lymphedema, and language impairment were positively associated with deletion sizes [ 5 ]. Moreover, 22q13.2q13.32 genomic regions were associated with the severity of speech delay, developmental delay, and physical features by statistical analysis in 70 patients with terminal 22q13 deletion [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SHANK3 gene has been identified as the critical candidate gene for the neurological features of this syndrome [2]. However, previous genotype-phenotype studies of PMS [3][4][5][6][7] and several case reports of 22q13 interstitial deletion [8][9][10] have implied the role of additional genes or regulatory regions proximal to the SHANK3 gene in PMS. Here, we report identical clinical and molecular findings from one pair of boy-girl twins with a de novo interstitial 22q13.31-q13.33 deletion not involving the SHANK3 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Although the prevalence of PMS is unknown, chromosome microarray and targeted resequencing of SHANK3 in ASD and ID suggest that up to 0.5–1% of subjects may show haploinsufficiency at this locus [58]. Because of its nonspecific clinical findings, the frequency of PMS is likely underestimated and is expected to increase with the widespread use of higher resolution microarrays and exome and genome sequencing with optimized coverage of SHANK3 [6, 7].…”
Section: Introductionmentioning
confidence: 99%